(untitled) (Marketing Journal, 2025)
This article analyzes advanced foreign experience in the application of digital technologies in housing stock management systems. In particular, effective housing management methods based on the concepts of the Internet of Things (IoT), Building Informatio n Modeling (BIM), Digital Twins, and Smart City are examined. Using the examples of Singapore, European Union countries, and Kazakhstan, the advantages of digital management mechanisms are revealed. Based on the analysis, practical proposals and recommenda tions for the digitalization of housing stock management in the Republic of Uzbekistan have been developed.